1998
DOI: 10.1136/oem.55.12.805
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for the assessment to quantitative dermal exposure limits in occupational environments: Part 2. Feasibility study for application in an exposure scenario for MDA by two different dermal exposure sampling methods.

Abstract: Objective-To evaluate two diVerent techniques for assessing dermal exposure to 4,4'-methylene dianiline (MDA) in a field study. The results were used to test the applicability of a recently proposed quantitative dermal occupational exposure limit (DOEL) for MDA in a workplace scenario. Methods-For two consecutive weeks six workers were monitored for exposure to MDA in a factory that made glass fibre reinforced resin pipes. Dermal exposure of the hands and forearms was assessed during week 1 by a surrogate skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…12 In this study a significant correlation was found between cumulative MDA excretion in urine and the results of the dermal exposure measurements (assessed by hand washing). Testing for compliance was performed both by comparison between the MDA excreted in the urine and a BLV, and by comparison between the estimated external dermal exposure (hand wash method) and the external DOEL as derived in this report.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…12 In this study a significant correlation was found between cumulative MDA excretion in urine and the results of the dermal exposure measurements (assessed by hand washing). Testing for compliance was performed both by comparison between the MDA excreted in the urine and a BLV, and by comparison between the estimated external dermal exposure (hand wash method) and the external DOEL as derived in this report.…”
Section: Discussionmentioning
confidence: 50%
“…Both comparisons were in close agreement, the exposure was estimated to be 20%-25% of the BLV and DOEL, respectively. 12 As stated before, one of the first steps now is to develop criteria to set a priority list of chemicals for which a DOEL is a useful and necessary tool in occupational health risk management. For this purpose the publications of ECETOC and US EPA and others may provide some basic elements, but these need further development and evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The techniques for assessing dermal exposure can be divided into three categories (Brouwer et al, 1998;Cherrie et al, 2000) as follows.…”
Section: Introductionmentioning
confidence: 99%